Imunolocalização e alterações patológicas induzidas pela infecção por Strongyloides venezuelensis em camundongos geneticamente deficientes em MHC de classe I ou II - Gonçalves, Ana Lúcia Ribeiro (2007)
In the present study, we investigated the mechanisms involved in the immune response of Major Histocompatibility Complex class I or class II knockout mice (MHC I-/- or MHC II-/-), after S. venezuelensis infection. Wild-type C57BL/6 (WT), MHC II -/- and MHC I -/- mice were individually inoculated with 3.000 larvae (L3) of Strongyloides venezuelensis and sacrificed on days 1, 3, 5, 8, 13 and 21 post-infection (p.i.). Samples of blood, lung and small intestine were collected. The specimen were routinely processed and stained with hematoxylin-eosin for the pathological analysis. The presence of the parasite antigen was demonstrated by immunoperoxidase analysis. MHC II-/- mice presented a significantly higher number of adult worms recovered from the small intestine on day 5 p.i. (p < 0,001) and presented elevated numbers of eggs in feces. The infection by S. venezuelensis was completely eliminated after 13 days of infection in WT as well as in MHC I -/-. In MHC II -/- eggs and adult worms were still found on day 21 p.i., however with a significant reduction in their number. Leukocyte counts were higher in the peripheral blood of MHC I -/- and MHC II -/- mice, mainly on day 3 p.i. (p< 0.05) when compared toWT. The analysis of the duodenal mucosa confirmed the presence of the parasite in all mice. In the lung, the antigen presence was observed in MHC I-/- mice on day 1 p.i. and in MHC II-/- mice, on days 1 and 5 p.i. In the small intestine of WT mice, it was observed a higher number of parasites on day 8 p.i. and their absence after 13 p.i. In MHC II -/- mice, the number of parasites in the duodenum was reduced on day 8 p.i., when compared to infected WT mice, however, the parasite antigen was detected in the inferior portions of the small intestine, what did not happen in the WT. These findings contribute for a better understanding of an immunodeficient host s immune response and present potential clinical application, since the methodology used in the experimental model allows a results extension towards the delineations of immune response in both animal and human infection.